Past and future of multiculturalism in Southeast Europe - Stanković-Pejnović Vesna (Međunarodni Problemi)
Multiculturalism is a logical extension of the politics of equal respect and the politics of recognition but it is not an inheritance of modern liberal state. In the area of Southeast Europe multiculturalism is known through centuries. By the collapse of Yugoslavia, new countries prioritized the strengthening the central state and creation one nation state, deleted memory of multiculturalism of past. When 1993 European Union, through Copenhagen criterion, stipulates condition for accession (respect and protection national minorities), countries of Southeast Europe faced with the implementation of multicultural standards based on assumption that policy of recognition and promotion ethno-cultural diversity can enlarge human freedom, strengthen human rights and democracy. Unlike west federal models, cultural autonomy exclude territorial autonomy, but include institutional autonomy, local government and right to use mother tongue. Models of the multicultural policy are numerous and dependable on political, social and cultural circumstances, but countries of Southeast Europe must accept multicultural future.